Conjuring a cooler world? Blockchains, imaginaries and the legitimacy of climate governance - Malcolm Campbell-Verduyn (University of Duisburg-Essen, Käte Hamburger Kolleg / Centre for Global Cooperation Research (KHK/GCR21), 2021)
Meeting on the second anniversary of the Paris Agreement signing in 2017, the United Nations Climate Change Secretariat founded the Climate Chain Coalition (CCC). Backed by a number of multi-stakeholder groups like the Blockchain for Climate Foundation, the Ottawa-based CCC promotes the 'blockchainization' of the Paris Agreement. What kind of 'cooler' world do blockchain-based climate governance projects conjure? This paper scrutinizes the shared visions materializing across climate finance experiments, locating them largely within existing individualistic imaginaries rather than more collectivistic alternatives. It finds the imaginaries of 'cool' technological experimentation to fall short in materializing broader input and more effective output required to overcome the legitimacy crisis facing market-led climate governance.
urn:nbn:de:hbz:464-20210526-115112-2
Keywords: 320; Blockchain; Technology; Finance; Governance; Legitimacy